Bioativação de água mineral com adição de microcápsulas de suco de maracujá amarelo (Passiflora edulis) obtidas pelo processo de gelificação iônica - Morais, Alaíza Barros Lima (2015)
The ionic gelation is a technique of microencapsulation by a reaction between a polymer solution and an ionic solution. This technique can protect the nutraceutical bioactive compounds. This study used the process of ionic gelation solution with sodium alginate in order to obtain a new product: a bioactive water from passion fruit microcapsules placed in the carbonated mineral water. The physical, physical-chemical, nutritional, microbiological, and microscopic stability were verified in the product packaged in glass bottles at 5 ± 1 ° C for 35 days. It was also observed the perception of consumers toward the microencapsulation technology and nutritional claims of bioactive water. For the microcapsules, it was possible to verify that the levels of ascorbic acid and carotenoids decreased during the storage period, and phenols remained constant (p≤0,05). Microcapsules and water presented balance of the ascorbic acid, carotenoids and phenols levels (p≤0,05). Microbial contamination was not observed. The storage time of the product did not cause microscopic changes in the microcapsules surface. Sensory results indicate that consumers do not realize the risk microencapsulation technology, used to prepare the bioactive water, and appreciated its nutritional characteristics. This study showed the bioactivation of water through the migration of bioactive compounds of passion fruit microcapsules presents relevant nutritional characteristics. Furthermore, the new product revealed viable for future commercial and economic study.